Effectiveness of Acid Mine Water Testing Using Sparing at PT. Bara Alam Utama - Herfien; Eri Barlian; Indang Dewata; Mulya Gusman; Nur Efendi (Postgraduate, University of Mataram, 2024)
Sparing is a remote monitoring tool (telemetry) and is carried out in real-time via various different devices, as well as storing and displaying it on many device options. This research uses a quantitative descriptive method, which aims to present data related to the research object. The data sources used in this research consist of primary and secondary data sources. Where primary data is obtained from direct observation and measurements regarding pH values, Total Suspended Solid (TSS), Iron (Fe) and Manganese (Mn) metal content. Secondary data was obtained through literature relevant to the research and documentation during the research. The results obtained in May 2022 were 31.0 and 32.2 mg/l, in November 2022 upstream and downstream, namely 19 and 26.8 mg/l. Meanwhile, the pH value of the water in May 2022 in the upstream river still met The quality book is 6.03, while the pH value in the upstream and downstream rivers is 7.3 and 7.1, while in November 2022 the upstream and downstream pH will be 6.43 and 7.11. The iron (Fe) and manganese content is also relatively small both upstream and downstream, namely in May 0.323 and 0.284 mg/l and in November 2022 0.612 and 0.124. Meanwhile, the results of the river pollution capacity are TSS on the Kungkilan River, namely (28.89 - 36.13 mg/L) and the Lematang River, namely (27.00 - 30.25 mg/L).